2012
DOI: 10.3917/cm.086.0197
|View full text |Cite
|
Sign up to set email alerts
|

L'extimité de l'étranger

Abstract: La question de l'étranger dont l'abord suscite bien des pièges imaginaires et des préjugés, peut être entendue différemment selon le registre de significations auquel elle est référée . D'un point de vue commun l'étranger désigne ce qui n'est pas familier. C' est pourtant le plus proche qui expose à l'inquiétante étrangeté. Freud nous invite à y repérer la manifestation de l'inconscient .Dans "Nouvelles conférences d'introduction à la psychanalyse" 1 il écrit : "Le refoulé est toutefois pour le moi, une terre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Instead, it is projected outside or perceived as a threat to be dealt with. This refusal has nefarious effects on both the subject and the social link, as evidenced by everyday clinical experience with individuals who perceive the enigma within themselves as a handicap, one that they sometimes try to displace onto others not like them, in a furious effort to draw a line between the inside and the outside, to fetishize difference (STITOU, 2012). In my experience, their suffering often manifests as an inhibition, an inability to construct or create.…”
Section: The Experience Of Initiationmentioning
confidence: 93%
“…Instead, it is projected outside or perceived as a threat to be dealt with. This refusal has nefarious effects on both the subject and the social link, as evidenced by everyday clinical experience with individuals who perceive the enigma within themselves as a handicap, one that they sometimes try to displace onto others not like them, in a furious effort to draw a line between the inside and the outside, to fetishize difference (STITOU, 2012). In my experience, their suffering often manifests as an inhibition, an inability to construct or create.…”
Section: The Experience Of Initiationmentioning
confidence: 93%
“…Generally, HL implementation research is conducted from the perspectives of consumers, government and companies or organisations. Stitou and Rezgui (2012), Kamaruddin et al (2012), Tieman et al (2013), Alqudsi (2014), Yusoff et al (2015), Fathi et al (2016), Masudin et al (2018) and Lestari and Gunita (2018) were some researchers who are conducting a study concerning the implementation of HL from a consumer’s perspective. Overall, the result of their research indicated the importance of HL for the Muslim community through their willingness to pay for HL and their loyalty, and they would not buy a product if they were in doubt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, the result of their research indicated the importance of HL for the Muslim community through their willingness to pay for HL and their loyalty, and they would not buy a product if they were in doubt. Stitou and Rezgui (2012) conducted a study in France’s Muslim community. The results revealed that 56% of 223 Muslim respondents would not buy a product if they were not sure about its halalness.…”
Section: Literature Reviewmentioning
confidence: 99%